Cooperative action of coherent groups in broadly heterogeneous populations of interacting chemical oscillators - Mikhailov, A. S. (National Academy of Sciences, 2004)
We present laboratory experiments on the effects of global coupling in a population of electrochemical oscillators with a multimodal frequency distribution. The experiments show that complex collective signals are generated by this system through spontaneous emergence and joint operation of coherently acting groups representing hierarchically organized resonant clusters. Numerical simulations support these experimental findings. Our results suggest that some forms of internal self-organization, characteristic for complex multiagent systems, are already possible in simple chemical systems.